First records of Lethocerus cfr. patruelis (Stål, 1854) from Calabria (southern Italy) (Hemiptera: Heteroptera, Belostomatidae) - Castiglione, Elvira; Lo Parrino, Elia; Manti, Francesco; Tomasi, Filippo (Fragmenta entomologica, 2021)
Lethocerus patruelis (Stål, 1854) is the only European member of the Belostomatidae family. During the last decades Lethocerus patruelis records have become frequent in south-eastern Italy, probably due to multiple accidental introductions or a natural westward spread of its range. The first records of Lethocerus cfr. patruelis for the Calabria region are here reported. The first individual was observed alive and photographed in Villapiana (Cosenza province), while the second one was found and collected in Prunella (Melito di Porto Salvo municipality, Reggio Calabria province). The status of Lethocerus patruelis in this region and in Italy as introduced or naturally spreading species is yet to be assessed.